Capacity Building Training for Elementary Teachers in Implementing Project-Based Ethno-STEM Assessment: A Case Study in Tasikmalaya, Indonesia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Indonesia, to design and implement culturally responsive project-based assessments using the Ethno-STEM approach. Ethno-STEM integrates science, technology, engineering, and mathematics with local cultural wisdom, offering students contextualized learning experiences connected to their sociocultural environment. The major challenges identified included teachers’ limited conceptual understanding of project-based assessment, minimal experience in constructing authentic assessment instruments, and the absence of practical models aligned with local cultural contexts. A mixed-methods design was employed through workshops, collaborative practice, mentoring, and field implementation in three partner schools with 45 participating teachers. Quantitative data were collected through pre–post tests, while qualitative insights were obtained from observations, reflection notes, and interviews. The findings revealed a substantial improvement in teachers’ competencies, with average scores increasing from 12.7 (adequate) to 22.8 (excellent). Teachers also demonstrated greater confidence, creativity, and cultural awareness in developing contextual assessment tools. This program contributes to strengthening teachers’ pedagogical professionalism and advancing culturally grounded STEM learning. The resulting assessment modules and teacher community of practice serve as sustainable outputs that can be replicated in other regions.